Interaction of social role functioning and coping in people with recent-onset attenuated psychotic symptoms: a case study of three Chinese women at clinical high risk for psychosis - Zhang TH (Dove Medical Press, 2015)
TianHong Zhang,1 HuiJun Li,2,3 Kristen A Woodberry,3 Larry J Seidman,3 Annabelle Chow,4 ZePing Xiao,1 JiJun Wang1 1Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Psychology, Florida A&M University, Tallahassee, FL, USA; 3Department of Psychiatry, Harvard Medical School, Beth Israel Deaconess Medical Center, Boston, MA, USA; 4Department of Psychological Medicine, Changi General Hospital, Singapore Abstract: Clinical high risk of psychosis is defined as the period in which the first signs of psychotic symptoms begin to appear. During this period, there is an increased probability of developing frank psychosis. It is crucial to investigate the interaction between psychotic symptoms and the individual’s personality and life experiences in order to effectively prevent, or delay the development of psychosis. This paper presents case reports of three Chinese female subjects with attenuated positive symptoms, attending their initial outpatient assessment in a mental health service, and their longitudinal clinical outcomes. Information regarding each subject’s symptoms and life stressors was collected at 2-month intervals over a 6-month period. The assessments indicated that these women were suffering from the recent onset of symptoms in different ways. However, all three hid their symptoms from others in their school or workplace, and experienced a decline in performance related to their social roles and in their daily functioning. They were often excluded from the social groups to which they had previously belonged. A decline in social activities may be a risk factor in the development of psychosis and a mediator of functional sequelae in psychosis. Effective treatment strategies may include those that teach individuals to gain insights related to their symptoms and a service that provides a context in which individuals can discuss their psychotic symptoms. Keywords: prodromal psychosis, ultra high risk, follow-up, functional sequelae, transition